2022
DOI: 10.3390/biom12010080
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Treatment: The Case of Gold(I)-Based Compounds as a Promising Class of Bioactive Molecules

Abstract: Breast cancers (BCs) may present dramatic diagnoses, both for ineffective therapies and for the limited outcomes in terms of lifespan. For these types of tumors, the search for new drugs is a primary necessity. It is widely recognized that gold compounds are highly active and extremely potent as anticancer agents against many cancer cell lines. The presence of the metal plays an essential role in the activation of the cytotoxicity of these coordination compounds, whose activity, if restricted to the ligands al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…In the Supporting Information (Table S4), we include tables with IC 50 values of gold precursors that could not be bioconjugated as well as IC 50 values in lung IMR90 fibroblasts (Table S5). We found that precursors ( 2a and 5a ) and NHS payloads ( 2c and 5c ) exhibited cytotoxicity against all cell lines in the low micromolar range (Table ), with some sensitivity toward MDA-MB-231, which can be explained by the high toxicity displayed by several gold­(I) phosphane-containing compounds against triple-negative breast cancers. After conjugation to trastuzumab and pertuzumab, both sets of ADCs ( Tras-2c , Per-2c , Tras-5c , and Per-5c ) exhibited higher cytotoxicity against cells overexpressing HER2 (BT-474 and SKBR-3) with IC 50 values in the submicromolar range. More significantly, for SKBR-3 cells, the IC 50 values for 2c and Tras-2c show a 10-fold increase in toxicity for the ADC.…”
Section: Resultsmentioning
confidence: 94%
“…In the Supporting Information (Table S4), we include tables with IC 50 values of gold precursors that could not be bioconjugated as well as IC 50 values in lung IMR90 fibroblasts (Table S5). We found that precursors ( 2a and 5a ) and NHS payloads ( 2c and 5c ) exhibited cytotoxicity against all cell lines in the low micromolar range (Table ), with some sensitivity toward MDA-MB-231, which can be explained by the high toxicity displayed by several gold­(I) phosphane-containing compounds against triple-negative breast cancers. After conjugation to trastuzumab and pertuzumab, both sets of ADCs ( Tras-2c , Per-2c , Tras-5c , and Per-5c ) exhibited higher cytotoxicity against cells overexpressing HER2 (BT-474 and SKBR-3) with IC 50 values in the submicromolar range. More significantly, for SKBR-3 cells, the IC 50 values for 2c and Tras-2c show a 10-fold increase in toxicity for the ADC.…”
Section: Resultsmentioning
confidence: 94%
“…The IC 50 values of 3 against the different HER2+ and HER2− cancer cell lines and IMR-90 were observed to be high (>60 μM), as previously reported for other cancer cell lines. 50 Encapsulating 3 into liposomes and immunoliposomes did not significantly affect viability. High IC 50 values of 54.7 ± 7.3 μM for Lipo- 3 and 52.6 ± 5.4 μM for Opt-Immunolipo-Tras- 3 were obtained.…”
Section: Resultsmentioning
confidence: 96%
“…This is expected, as the IC 50 of trastuzumab against all cell lines easily exceeds 50 μM. 23,50 Optimization of trastuzumab-based immunoliposome size for specific gold compounds With the previous experiments described, we have shown the facile preparation of gold-containing liposomes and demonstrated that engrafting specific mAbs onto these vehicles can induce targeting selectivity and toxicity toward cells overexpressing an antigen recognized by these mAbs. We showed these gold-containing lipo-and immunoliposomes to be <200 nm in diameter, a precondition for the EPR effect that allows nanoparticles to accumulate in tumor environments.…”
Section: Rsc Medicinal Chemistrymentioning
confidence: 84%
“…To improve gold­(I) compound pharmacokinetics, transport through the cell, tumor selectivity, lipophilicity, ,, and antitumoral activity against cisplatin resistant cancer cells, , we incorporated chiral phosphine ligands (L2–L5) or tricyclohexylphosphine (L6) into our metal-based drug candidates. Indeed, tricyclohexylphosphine (L6), widely used in biological systems, has been shown to exhibit the highest activity against cisplatin-resistant DU145 human prostate cancer cells among the studied complexes. , …”
Section: Resultsmentioning
confidence: 99%